Rapat Penelaahan Gerakan KB Nasional tahun 1990 : [risalah] (Badan koordinasi Keluarga Berencana Nasional Propinsi Sulawesi Tengah, 1990)
Evaluations of the national family planning programs in Sulawesi Tengah Province; results of a meeting.